Forest ecology of quaking aspen in Rocky Mountain National Park: a landscape survey, a reconstruction, and a predictive model - Kaye, Margot Wilkinson, author; Binkley, Dan, advisor; Stohlgren, Thomas J., committee member; Steingraeber, David A., committee member; Veblen, Thomas T., committee member (Colorado State University. Libraries, 2002)
Ecology and management issues of quaking aspen in western forests have come to a pinnacle in the region of Rocky Mountain National Park, Colorado. Human land-use practices over the past century have altered both fire regimes and elk populations, two factors that play important roles in the life history of aspen. Fire suppression diminished the number of new aspen stands, most aspen stands have reached 100 years of age, and many stands are succeeding to conifers. Previous studies of aspen in the Park have concluded that intensive elk browsing has brought about a decline in the aspen population. A survey of 240 hectares of the Park revealed that elk browsing has a highly localized effect on aspen populations in the heart of the elk winter range, but on a broader spatial scale, conifer invasion is more prevalent. A dendrochronological reconstruction of the dynamics of conifer invasion of aspen stands indicated that conifer trees replace aspen via sub-canopy establishment and longevity rather than directly causing a decline in aspen growth or an increase in aspen mortality. Forest succession from aspen to conifer forests primarily occurs due to differential life history traits of the species involved, rather than species interactions. Tree-ring data were used to create an age structured model for aspen in the Park. The model projects aspen density through time under varying recruitment scenarios. Aspen stands sampled in this study require between 100 and 300 stems ha-1 recruitment each decade to maintain current stand density (500 to 1500 stems ha-1). With no future recruitment, aspen stands would not persist longer than 100 years. Periodic pulses of recruitment lead to an aspen stand structure that is highly dynamic through time.
Keywords: ecology; forestry